Relacje łączące rodziną z familią w świetle teorii wymiany - Żurek, Aldona (Wydawnictwo Naukowe UAM, 2002)
Nuclear family is subject to more and more intensive processes of modernization. It changes her part in society, and it rules other assignments in life of individuals. One o f the theories, which permits on explanation this, which one place occupies family among other social structures is theory of exchange. The business of exchange is transacted among family members and also between family and other in society. Theory o f exchange is scientific study of the patterns of interrelationships between the family and nonfamily system. This theory gives possibility of qualification of power of influences different factors, different regarding of one’s own character. Analysis is possible both then, when her object is a social group, as then, when refer of behaviors of single people.
Relationships among nuclear family and extended family in light of theory of exchange